The celery genome sequence reveals sequential paleo‐polyploidizations, karyotype evolution and resistance gene reduction in apiales. Issue 4 (18th November 2020) - Song, Xiaoming; Sun, Pengchuan; Yuan, Jiaqing; Gong, Ke; Li, Nan; Meng, Fanbo; Zhang, Zhikang; Li, Xinyu; Hu, Jingjing; Wang, Jinpeng; Yang, Qihang; Jiao, Beibei; et al.
Summary: Celery ( Apium graveolens  L. 2 n  = 2 x  = 22), a member of the Apiaceae family, is among the most important and globally grown vegetables. Here, we report a high‐quality genome sequence assembly, anchored to 11 chromosomes, with total length of 3.33 Gb and N50 scaffold length of 289.78 Mb. Most (92.91%) of the genome is composed of repetitive sequences, with 62.12% of 31 326 annotated genes confined to the terminal 20% of chromosomes. Simultaneous bursts of shared long‐terminal repeats (LTRs) in different Apiaceae plants suggest inter‐specific exchanges. Two ancestral polyploidizations were inferred, one shared by Apiales taxa and the other confined to Apiaceae. We reconstructed 8 Apiales proto‐chromosomes, inferring their evolutionary trajectories from the eudicot common ancestor to extant plants. Transcriptome sequencing in three tissues (roots, leaves and petioles), and varieties with different‐coloured petioles, revealed 4 and 2 key genes in pathways regulating anthocyanin and coumarin biosynthesis, respectively. A remarkable paucity of NBS disease‐resistant genes in celery (62) and other Apiales was explained by extensive loss and limited production of these genes during the last ~10 million years, raising questions about their biotic defence mechanisms and motivating research into effects of chemicals, for example coumarins, that give off distinctive odours. Celery genome sequencing and annotation facilitates further research into important gene functions and breeding, and comparative genomic analyses in Apiales.